Cytotoxic and Cell progression Effects of Mentha pulegium L Extract on Selected Cancer Cell Lines: Cytotoxicity of Mentha pulegium L extract on selected cancer cell lines - Farnam, Golrokh; Aryanpour, Narges; Behtaj, Reyhaneh; H. Shirazi, Farshad (Iranian Journal of Pharmaceutical Sciences, 2020)
Mentha pulegium L. is one of the Mentha (Labiatae) species that is grown in many different parts of the earth including northern Iran. The total ethanolic extract of the aerial parts of this plant is used in this work to investigate on the possible cytotoxicity on two different cell lines. Human lung carcinoma cells (A549) and human breast cancer (MCF7), have been used to show the clonogenic count of cells, as well as their cell cycle phases progression pattern after the exposure to the different concentrations of this extract. The cytotoxicity of the total extract of Mentha pulegium L. is 59 ± 1.73 μg/ml for the MCF7, and 48.86 ± 2.5 μg/ml for the A549 cell lines, respectively. Flow cytometry analysis have shown two different adventures for these cell lines after 24 hours exposure to this extract. While the MCF7 cells presented a dose-dependent arrest at the G2/M phase of the cell cycle, the A549 cells are more intended to accumulate in the so-called G0 resting phase after the exposure to this extract. These promising initial results might bring hope for the introduction of a tissue discriminating anticancer agent in future.